The Relation Between Psycholinguistics and Gender - Wafa Kazim Hussein; Abdullah Hussein Rasool (QALAAI ZANIST JOURNAL, 2023)
This research is under the title of (The relation between psychological linguistics and gender) it’s an attempt for indicating the affection of language about individuals inner mind and this inflexibility that will be created in psychological condition. If it is in the form of positive or negative will be affected. The individual meets themselves in a different psychological condition. Because when human being comes to the world will be born with a specified characteristics female or male. But it is not held the aspects of male and female. But this is the affection of educational language and developing society about psychological matters in any individual and giving roles with different personality to each male and female gender., reflecting on individuals’ behavior (male and female) generally and and specifically language behavior. Any individual will give the speech according to psychological condition that he or she lives in. This research consists of two parts: in the first part it talks about the relation between language and psychology, the theory of psychological linguistics, terms and the definition of psychological linguistics, the differentiate psychological linguistic and psychology of language. History of revolution and developing psychological linguistics. psychological linguistic is linked to the sociological linguistic. The second part of the research is dedicated to acknowledging gender and the theory of gender, then the thesis of the research and in the end the resources are demonstrated.